Pueblos antiguos, ciudad diversa. Una definición etnográfica de los pueblos originarios de la Ciudad de México - Medina Hernández, Andrés (Annals of Anthropology, 2010)
This essay propounds a definition of pueblos originarios from Mexico City departing from ethnographic data assembled from fieldwork research and available bibliography. The proposal assumes a dinamic configuration characteristic based on the ancient mesoamerican communities from the Basin of Mexico that confront different presures of urban growth. In this resisting and negotiating process these communities are transformed. Some of them are disintegrated but the majority achieve to reproduce and reinvent/readapt themselves depar-ting from a cultural capital contained in the mesoamerican tradition. Nevertheless the urban growth of the city still threatens them to wich they have responded by self-determining and recovering themselves together with the indian peoples movement the right to their cultural specifities and to their political representation in political instances.